An Environmental Ethics in Islamic Perspective: An Analysis of the Thoughts of Dr. Sayyed Hossein Nasr - Lesi, Alda Tanpa; Alfatih, Fajrul (International Journal on Advanced Science, Education, and Religion, 2025)
The global environmental crisis is getting more complex, and attention to environmental ethics is becoming important. This article analyzes Dr. Sayyed Hossein Nasr about environmental ethics in Islam. This study uses the method of literary analysis by using the writings and speeches of Dr. Nasr as the main source. The research results show that Dr. Nasr regards environmental ethics as an integral part of Islamic teachings. He emphasized how important it is to maintain harmony between humans and nature, social and economic justice, and the fair management of natural resources. His thoughts provide valuable insights for society in maintaining harmony between humans and nature, and creating a sustainable environment. The implications are relevant in the face of current climate change and environmental degradation. To apply this thinking, it is necessary to increase environmental awareness, the active role of religious leaders, cooperation between Muslim countries, and a combination of scientific knowledge. This thinking can have a positive impact on environmental preservation for future generations.